The Narrative of Cabeza de Vaca - Núñez Cabeza de Vaca, Alvar, active 16th century (Book collections on Project MUSE., 2003)
This edition of Álvar Núñez Cabeza de Vaca's Relación offers readers Rolena Adorno and Patrick Charles Pautz's celebrated translation of Cabeza de Vaca's account of the 1527 Pánfilo de Narváez expedition to North America. The dramatic narrative tells the story of some of the first Europeans and the first-known African to encounter the North American wilderness and its Native inhabitants. It is a fascinating tale of survival against the highest odds, and it highlights Native Americans and their interactions with the newcomers in a manner seldom seen in writings of the period. In this English-language edition, reproduced from their award-winning three-volume set, Adorno and Pautz supplement the engrossing account with a general introduction that orients the reader to Cabeza de Vaca's world. They also provide explanatory notes, which resolve many of the narrative's most perplexing questions. This highly readable translation fires the imagination and illuminates the enduring appeal of Cabeza de Vaca's experience for a modern audience.